Plant invasions on small Mediterranean islands: An overview. (2nd September 2016) - Celesti-Grapow, L.; Bassi, L.; Brundu, G.; Camarda, I.; Carli, E.; D'Auria, G.; Del Guacchio, E.; Domina, G.; Ferretti, G.; Foggi, B.; Lazzaro, L.; Mazzola, P.; et al.
Abstract: Biological invasions have become one of the main drivers of habitat degradation and a leading cause of biodiversity loss in island ecosystems worldwide. The spread of invasive species poses a particular environmental threat on the islands of the Mediterranean Basin, which are hot spots of biodiversity and contain rare habitats and endemic species, especially on small islands, which are highly vulnerable to biodiversity loss. Following a recent survey, in this paper we aim to provide an overview of the present-day non-native vascular flora of small Mediterranean islands based on a sample of 37 islands located in the middle of the Mediterranean Sea, off the coast of Italy. By comparing the current data with those gathered during a previous survey conducted in the same study area, we also aim to highlight the main changes that have occurred in non-native plant species diversity, establishment and distribution in recent years and to present a first general overview of the most prominent plant taxa in the island's introduced flora, focusing on those most responsible for these changes and those that pose the greatest environmental threats. We recorded 203 non-native plant species, 147 of which have established on at least one of the islands investigated. Overall, we detected a sharp increase in the number of species, in their levels of establishment and in the extent of their distribution within the study area in recent years. This may be explained by the intensification of research on plant invasions, as well as to new introduction, escape, establishment and invasion events on the islands in recent decades. The most remarkable plants detected include acacias and succulents, two groups that appear to be emerging very rapidly and to be posing new threats to the conservation of the islands' natural environment, especially the genus Carpobrotus, whose spread into natural habitats containing rare and endemic taxa is seriously threatening biodiversity on both a local and global scale. On the whole, our results show that the plant invasion phenomenon in the study area has in recent years intensified considerably. As this process seems likely to continue, we should expect more establishment events in the future and the further spread of species that are already present. This is of particular conservation concern on the islands investigated in this survey, which are rich in endemisms, but have been facing deep socio-economic and environmental transformations in these last decades as a consequence of the abandonment of traditional management practices and the development of tourism. Our study thus confirms that plant invasions on Mediterranean islands are a serious environmental problem that threatens biodiversity conservation not only in the Mediterranean biogeographic region, but also on the global scale, and highlights the need to further increase efforts aimed at preventing, controlling or mitigating the effects of plant invasions in island ecosystems.